Analysis of the Influence of Website Quality and CSR on Trust and Its Impact on Repurchase Intention (Case Study: PT.Antam UBPP Precious Metal) - Sarah Bulqis, Andi Nurul (Bina Nusantara University, 2022)
The purpose of this research is to know the influence of the Quality of the Website and CSR against Trust as well as its impact on Repurchase Intention. In this study, PT. Antam UBPP Logam Mulia used as an example of the case. This research is associative research and aims to achieve the goal of researchers. Research done by providing a questionnaire that was distributed directly to consumers the seventy PT. Antam UBPP Logam Mulia by using the technique of taking the Census sample. Data analysis using Structural equation modeling – Partial Least Square (SEM-PLS) is used for the data analysis techniques. This research proves that the Web Quality affect Trust, CSR affect Trust, Website Quality affects Repurchase Intention, CSR affects Repurchase Intention, Trust affects Repurchase Intention. The result of this research provides benefits to the company (PT. Antam UBPP Logam Mulia), in which the results of this research can be used to define the strategy of the company and create the perception of the true value of product or consumer company PT. Antam UBPP Logam Mulia.